Global change feed-back linking water transparency, mixing, and solar UVR inhibits cyanobacterial photosynthesis - Helbling, Eduardo Walter (2015)
Cyanobacteria are an important component of aquatic ecosystems, with a proliferation of massive cyanobacterial blooms predicted worldwide under increasing warming conditions. In addition to temperature, other global change related variables, such as water column stratification, increases in dissolved organic matter (DOM) discharge into freshwater systems and greater wind stress (i.e., more opaque and mixed upper water column/epilimnion) might also affect the responses of cyanobacteria. However, the combined effects of these variables on cyanobacterial photosynthesis remain virtually unknown. Here we present evidence that this combination of global-change conditions results in a feed-back mechanism by which, fluctuations in solar ultraviolet radiation (UVR, 280–400 nm) due to vertical mixing within the epilimnion act synergistically with increased DOM to impair cyanobacterial photosynthesis as the water column progressively darkens. The main consequence of such a feed-back response is that these organisms will not develop large blooms in areas of latitudes higher than 30°, in both the Northern and Southern Hemispheres, where DOM inputs and surface wind stress are increasing.